Phase transitions and thermodynamics of quasione- dimensional quantum rotor and spin systems - Sandoildo Freitas Tenório, Antônio (2009)
Sandoildo Freitas Tenório, Antônio; Domingues Coutinho Filho, Maurício. Phase transitions and thermodynamics of quasione- dimensional quantum rotor and spin systems. 2009. Tese (Doutorado). Programa de Pós-Graduação em Física, Universidade Federal de Pernambuco, Recife, 2009.